Electrocatalytic cleavage of lignin model dimers using ruthenium supported on activated carbon cloth. Issue 3 (7th January 2020) - Garedew, Mahlet; Young-Farhat, Daniel; Bhatia, Souful; Hao, Pengchao; Jackson, James E.; Saffron, Christopher M.
Abstract : Thermally resistant 4-O-5 linked lignin model dimers are cleaved to valuable intermediates under mild conditions with high faradaic efficiency. Abstract : Biomass lignin is the largest natural source of renewable aromatic compounds, creating an opportunity for its use as a feedstock provided that deconstruction and upgrading methods become available. Valorization of lignin is challenging because its complex structure is naturally recalcitrant to biological degradation. Deconstruction of this amorphous cross-linked polymer requires cleavage of aryl ether bonds, which account for more than half of the linkages between lignin's phenylpropanoid building blocks. High temperature cracking of lignin is possible via pyrolysis, but linkages such as 4-O-5 bonds are resistant to thermal degradation. Electrocatalytic hydrogenation offers a mild alternative; operated at low temperature and atmospheric pressure, it cleaves ether bonds while saturating aromatic rings with in situ generated hydrogen. To investigate the use of catalytic ruthenium supported on activated carbon cloth to cleave 4-O-5 bonds, model compounds that exhibit this linkage were selected, including 3-phenoxyphenol, 4-phenoxyphenol, 3-phenoxyanisole, and 3-phenoxytoluene. The two phenols, 3-phenoxyphenol and 4-phenoxyphenol, were cleaved and hydrogenated to form cyclohexanol. 3-Phenoxyanisole and 3-phenoxytoluene were also cleaved but with lower conversion rates and cyclohexanol yields. Alkaline electrolyte solutions showed the highest cyclohexanol yields for both substrates. Increasing substrate concentrations from 10 mM to 40 mM increased faradaic efficiency to 25%, while decreasing current density from 100 mA (33.33 mA cm −2 ) to 20 mA (6.67 mA cm −2 ) greatly improved the faradaic efficiency to 96%.